2021
DOI: 10.1016/j.childyouth.2020.105912
|View full text |Cite
|
Sign up to set email alerts
|

Immediate psychological responses during the initial period of the COVID-19 pandemic among Bangladeshi medical students

Abstract: Highlights This is the first study to investigate the mental health status of Bangladeshi medical students during COVID-19 pandemic. The HADS anxiety subscale revealed that 65.9% of the medical students had different levels of anxiety, ranging from mild (27.3%), moderate (26.8%), and severe (11.8%). As per HADS depression subscale, 49.9% of the medical students had varying degrees of depressive symptoms, with 3.3% of the participants had suffered from seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
103
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 58 publications
22
103
3
1
Order By: Relevance
“…It is possible that some individuals had a previous history of depression and therefore the data captured might not be due to COVID-19. However, our data agree with published data on depressive symptoms during COVID-19 in Bangladesh in the general population (47.2%) [ 30 ], healthcare workers (39.5%) [ 25 ], and medical students (49.9%) [ 31 ]. It may not be valid to compare pre-COVID rates of depression, as cohorts may be different and there could be significant variations in demographic factors such as age, sex, marital status, and other features.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is possible that some individuals had a previous history of depression and therefore the data captured might not be due to COVID-19. However, our data agree with published data on depressive symptoms during COVID-19 in Bangladesh in the general population (47.2%) [ 30 ], healthcare workers (39.5%) [ 25 ], and medical students (49.9%) [ 31 ]. It may not be valid to compare pre-COVID rates of depression, as cohorts may be different and there could be significant variations in demographic factors such as age, sex, marital status, and other features.…”
Section: Discussionsupporting
confidence: 91%
“…Then, they (RAs) were properly instructed to share our survey link among their family members, friends, colleagues, and other peers who had recovered from COVID-19. This technique has been used in previous research in Bangladesh [ 31 ]. Approximately 1200 individuals were invited to participate in the survey, of whom 1083 individuals took part.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies considering the university students found the rate to be within 72% to 82.4%, 33 , 34 , 36 whereas 49.9% was reported for medical students. 32 Also, a 61.9% prevalence rate of depression was identified in a study, although detail about the student status was not mentioned in that study. 31 …”
Section: Resultsmentioning
confidence: 89%
“…In addition, nearly half of the medical students in the United Arab Emirates had mild to severe anxiety symptoms ( N = 1,485, GAD-7 ≄ 5) in March 2020 ( 19 ). During the initial period of the COVID-19 pandemic, 49.9% of 425 Bangladeshi medical students reported anxiety and 69.9% of them were with depressive symptoms through an online survey using the Hospital Anxiety and Depression Scale ( 20 ). A survey conducted in the United States ( N = 741) also showed that COVID-19 disrupted medical education and clinical training and that medical students experienced moderate stress and anxiety, which was measured using one Likert item ( 2 ).…”
Section: Introductionmentioning
confidence: 99%